2016
DOI: 10.3390/ma9110929
|View full text |Cite
|
Sign up to set email alerts
|

Freckle Defect Formation near the Casting Interfaces of Directionally Solidified Superalloys

Abstract: Freckle defects usually appear on the surface of castings and industrial ingots during the directional solidification process and most of them are located near the interface between the shell mold and superalloys. Ceramic cores create more interfaces in the directionally solidified (DS) and single crystal (SX) hollow turbine blades. In order to investigate the location of freckle occurrence in superalloys, superalloy CM247 LC was directionally solidified in an industrial-sized Bridgman furnace. Instead of cera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…It is known that many types of defects in single-crystalline (SX) turbine blades are created during directional crystallization by the Bridgman technique, while the crystallization front passes through areas with abrupt changes in a geometry of the cast [1,2,3,4,5,6,7,8]. The layers of the blade root located near the plane of connection with a selector (selector-root (S–R) connection), where branching of the primary dendrite arms and lateral growth occur, are especially important for defects creation [9,10,11,12,13,14]. In these layers, the low-angle boundaries (LABs), related to the local crystal misorientation, are created [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that many types of defects in single-crystalline (SX) turbine blades are created during directional crystallization by the Bridgman technique, while the crystallization front passes through areas with abrupt changes in a geometry of the cast [1,2,3,4,5,6,7,8]. The layers of the blade root located near the plane of connection with a selector (selector-root (S–R) connection), where branching of the primary dendrite arms and lateral growth occur, are especially important for defects creation [9,10,11,12,13,14]. In these layers, the low-angle boundaries (LABs), related to the local crystal misorientation, are created [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was found that the casting size was influential in the formation of freckle defects. Giamei et al [6] and Hong et al [17] showed that the freckle chains in the larger diameter single-crystal bars were more than those in the smaller diameter bars during the same solidification process. In addition, casting geometry can also influence freckle formation.…”
Section: Introductionmentioning
confidence: 99%
“…The process of making subsequent layers in a casting mould using the lost-wax process requires the use of appropriate binding agents to ensure the production of ceramic moulds with adequate parameters, i.e., high heat resistance, mechanical strength, gas permeability, dimensional stability, and required surface smoothness of the first layer [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. The basic materials for the production of sand and ceramic casting moulds are binders, ceramic powders, and auxiliary materials, i.e., agents that limit foaming during mixing, wetting agents, pH stabilizers, and modifiers of rheological properties of the ceramic slurry [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%